(untitled) - Neil McBurbey (New York, 1996)
The book features up-to-date authentic professional texts, wide-ranging coverage of the field of international tourism, contextualised exercises offering a wide range of techniques for developing effective reading skills, glossary of professional vocabulary.
Keywords: english langfuage - textbooks for foreign speakers,hospitality industry - problems, exrcise, etc,readers - hospitality industry,readers - tourist trade,tourist trade - problems, exrcise, etc